Role of Supervisors in Improving Islamic Education Teachers’ Professionalism During Covid-19 Pandemic - Sinar, Sinar (SUKMA: Jurnal Pendidikan, 2021)
The quality of teacher teaching focuses on two aspects, namely in terms of process and in terms of results. This study aimed to determine (1) the implementation of learning in the target area of the district Cluwak, Gunungwungkal, Margoyoso and Wedarijaksa in 2020-2021, (2) increasing Islamic Education teachers’ professionalism in the target area of the district. Cluwak, Gunungwungkal, Margoyoso and Wedarijaksa for 2020-2021, and (3) the role of supervisors in increasing the professionalism of Islamic Education teachers during the Covid-19 pandemic. This study was focused on primary education teachers carried out with a supervisory research approach (Action Research). This study used two cycles that contained planning, action, observation, and reflection in each cycle. This study used analytical descriptive research as data processing/analysis. This study showed that Islamic Education Supervisors and Principals always provide supervision, both through class visits, and in teacher coaching in online KKG forums. The supervision material includes 2 components, namely the development of knowledge about the professionalism of Islamic Education teachers and academic observation materials.